PENERAPAN METODE READING CORNER UNTUK MENINGKATKAN HASIL KETERAMPILAN MEMBACA PADA KELAS II DI SDN LAKARSANTRI III/474 SURABAYA - Fida Munawwaroh; Suprayitno; Selvia Nendy Afriliana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to determine the level of difficulty in reading class II and to determine the improvement in the results of implementing Reading Corner on class II reading skills at SDN Lakarsantri III/474 Surabaya. The background to this research is that there are students who have difficulty reading so that in learning these children are left behind because they cannot read. This is a concern for teachers to pay attention to these students. Reading is one of the language skills that students must have.  Therefore, special attention needs to be paid to students who are lagging behind in reading skills. The type of research used is Collaborative Class Action Research (PTKK). This research uses qualitative research with case studies. The stages in a classroom action study consist of: planning stage, implementation stage, observation stage and reflection stage. The results of this research are 1) In class II, 6 students were found who had reading difficulties. Of the 6 students, 2 students did not recognize the letters of the alphabet A-Z. Meanwhile, 4 students have delays in reading. 2) After implementing the Reading Corner, students' reading skills improved with the acquisition of data that had a value above the KKM, namely 15 students with a total of 17 students. Meanwhile, before implementing the Reading Corner, there were 9 students who had scores above the KKM.